Analisis Keberlanjutan Pertanian Kopi Arabika di Kecamatan Lembah Gumanti Kabupaten Solok - Putra, Muhamad Fajri Hena; U, Iswandi (Lembaga Yasin AlSys, 2026)
Strategic environmental changes necessitate the sustainable management of coffee farming systems. As a high-value flagship commodity, coffee faces various challenges that trigger fluctuations in production and farmers’ income, making the study of coffee farming sustainability increasingly important. This study aimed to identify and analyze the sustainability of arabica coffee farming in Lembah Gumanti Subdistrict based on five sustainability dimensions—ecological, economic, social, technological and infrastructural, and institutional—while also identifying sensitive attributes that influence this sustainability. A quantitative approach was employed using simple random sampling of 60 arabica coffee farmers. The analysis was conducted using the Rapfish method through a multidimensional scaling (MDS) approach. The data comprised primary data collected through interviews with farmers and secondary data obtained from relevant agencies and literature. The multidimensional analysis showed that the sustainability status index of arabica coffee farming in Lembah Gumanti Subdistrict was 57.21, which falls into the moderately sustainable category. The sustainability indices by dimension indicated that the ecological dimension (69.15), economic dimension (75.00), and technological and infrastructural dimension (53.28) were in the moderately sustainable category, whereas the social dimension (47.27) and institutional dimension (38.35) were in the less sustainable category. Of the 26 indicators used, 10 were identified as sensitive attributes that significantly influenced the sustainability of arabica coffee farming. These findings underscore the importance of enhancing sustainability through targeted interventions focusing on these sensitive attributes in order to improve the index and sustainability status of arabica coffee farming in Lembah Gumanti Subdistrict.